ARGET-ATRP synthesis and swelling response of compositionally varied poly(methacrylic acid-co-N, N-diethylaminoethyl methacrylate) polyampholyte brushes. Issue 30 (17th July 2018) - Ramirez, Rachel; Woodcock, Jerimiah; Kilbey, S. Michael
Abstract : Local comonomer sequence of random polyampholyte brushes synthesized by ARGET ATRP facilitates ionization and promotes self-neutralization across a wide pH range, including in the presence of an added osmolyte. Abstract : Modifying the composition of polyampholytes, which are comprised of charge-positive and charge-negative repeat units, directly contributes to trade-offs between charge and structure, which are externally regulated by solution pH and added salt. Here, the relative ratio of anionic and cationic comonomers is varied to tailor the stimuli-responsiveness of poly(methacrylic acid- co-N, N -diethylaminoethyl methacrylate) (P(MAA- co -DEAEMA)) brushes to changes in solution pH and an added zwitterion. These systems display a strong dependence on excess repeating units of either type and the random incorporation appears to facilitate self-neutralization of charges. Pseudo-living growth with smooth comonomer incorporation is achieved using activators regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP), creating well-defined brushes. In situ ellipsometry measurements of solvated brush thickness indicate that at low and high pH, the brushes display polyelectrolyte behavior with a strong compositional dependence, but at intermediate pH values, the brushes show the characteristic collapse attributed to self-neutralization of polyampholytes. The polyampholyte brushes maintain these patterns of behavior across all compositions and in the presence of an added zwitterion, which contributes additional hydrophobic character as evidenced by decreases in the swollen layer thicknesses. The response of the P(MAA- co -DEAEMA) brushes to the organic osmolyte betaine is consistent with its tendency to stabilize proteins and peptides in a kosmotropic fashion. These studies add perspective to efforts to manipulate sequence in polyampholytic polymers, support broader efforts to tailor interfacial soft films for applications in biotechnology and sensing, and understand aggregation and stability of biological polymers.